Preservation of a highly perishable food, watermelon juice, at and above room temperature under mild pressure (hyperbaric storage) as an alternative to refrigeration - Santos, M.D. (2022)
The feasibility of food preservation under pressure (hyperbaric storage) at and above room temperatures, as an alternative to refrigeration was evaluated. Preservation of a highly perishable food, watermelon juice, was studied at pressures of 25e150 MPa and temperatures ranging 20e37 C, being compared to refrigeration and storage at atmospheric pressure at the same temperatures. Hyperbaric storage at 75 MPa (20e37 C) revealed an inhibitory effect on microbial growth, with at least an equal performance compared to refrigeration. An additional inactivation effect was verified for storage at 100 and 150 MPa, with reduction of the initial microbial counts to 1.00 Log CFU/mL for enterobacteriaceae and yeasts and moulds, and from 4.43 ± 0.04 to 3.31 ± 0.04 and 2.99 ± 0.07 Log CFU/ mL, respectively, for total aerobic mesophiles (25 C). In general, pH, titratable acidity and total soluble solids did not show a clear variation trend with pressure and no considerable differences among storage conditions were verified. Cloudiness decreased for samples stored under pressure and browning degree was in general lower in samples stored under pressure compared to refrigeration. This work demonstrates the potentiality of hyperbaric storage as a new preservation methodology, at variable (uncontrolled) room temperature without energetic costs during storage, as an alternative to refrigeration.